Exploring the Capability of Fish Waste-Derived Oil as a Sustainable Biofuel Option - Bindu Devi, Karthikeyan MP, Chetan Chaudhary (Revista Electronica de Veterinaria, 2024)
The rapidly increasing global energy demand, along with the rapid depletion of non-renewable fossil fuels, needs a coordinated effort to investigate alternate and sustainable energy sources. Biofuels generated from diverse biological sources, such as biodiesel, bio-ethanol, bio-butanol and bio-hydrogen, have emerged as similarly fascinating alternatives in this environment. Among them, the exploitation of biological wastes, notably from fish, gives a compelling alternative. Despite substantial studies on biodiesel production from plant, algal and microbial sources, there is an enormous gap in understanding regarding the effective conversion of fish waste into biodiesel. This analysis assesses the sustainability of fish waste-derived oil as a biofuel source, highlighting the requirement for efficient biodiesel manufacturing processes. Despite its environmental as well as economic benefits, inadequate knowledge and limited attempts to convert fish waste to biodiesel restrict advancement in this sector. In compliance with PRISMA principles, a systematic review was performed. After an extensive search was conducted using the databases of PubMed, Web of Science and Google Scholar, 200 pertinent studies were found. Once the inclusion criteria were applied, 15 papers were chosen for examination. Unrealized potential for meeting waste management and energy demands is revealed by the investigation of oil produced from fish waste as a biofuel alternative. The Physicochemical parameters that affect fish oil production for biodiesel waste are discovered, providing information regarding essential components for effective conversions. The results encourage further investigations into fish waste as a useful resource for the manufacture of bio-fuels and they are by international initiatives to create environmentally friendly along with renewable energy alternatives.